Relationship of Freshwater Aquaculture Production to Renewable Freshwater Resources - Boyd, Claude E.; Li, Li; Brummett, Randall (Taylor and Francis, 2013)
At the country-level, freshwater aquaculture production was correlated (P 1,000 ton/km3 (n = 12). Most renewable freshwater isin countries with no freshwater aquaculture or low AFR; countries with high AFR contain 11.1% of global renewable freshwater. By FAO region, AFR values were: Oceania,1.56 ton/km3; Latin America and Caribbean, 31.1 ton/km3; North America, 50.0 ton/km3; Europe, 68.7 ton/km3; Africa, 84.1 ton/km3; and Asia, 2,409 ton/km3. Renewable freshwater appears adequate for considerable expansion of aquaculture, especially outside Asia.